Direct and residual effects of organic and inorganic fertilizers on soil chemical properties, microbial components and maize yield under long-term crop rotation - Claassens, A.S. (Andries Stephanus), 1943- (University of Pretoria, 2013)
Thesis (PhD (Plant Production and Soil Science))--University of Pretoria, 2003.